2004
DOI: 10.2169/internalmedicine.43.1171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel Missense Mutations (p.R1221C and p.R1357W) in the ABCC6 (MRP6) Gene in a Japanese Patient with Pseudoxanthoma Elasticum (PXE)

Abstract: Pseudoxanthoma elasticum (PXE) is a rare, inherited, systemic disease of elastic tissue that in particular affects the skin, eyes, and cardiovascular system. Recently, the ABCC6 (MRP6) gene was found to cause PXE. A defective type of ABCC6 gene (16p13.1) was determined in two Japanese patients with PXE. In order to determine whether these patients have a defect in ABCC6 gene, we examined each of 31 exons and flanking intron sequences by PCR methods (SSCP screening and direct sequencing). We found two novel mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
(18 reference statements)
4
11
0
Order By: Relevance
“…To date, more than 150 mutations in ABCC6 have been reported [Bergen et al, 2000;Le Saux et al, 2000;Ringpfeil et al, 2000;Struk et al, 2000;Le Saux et al, 2001;Cai et al, 2001;Meloni et al, 2001;Ringpfeil et al, 2001;Le Saux et al, 2002;Hu et al, 2003b;Chassaing et al, 2004;Gheduzzi et al, 2004;Noji et al, 2004;Chassaing et al, 2005;Hendig et al, 2005;Katona et al, 2005;Miksch et al, 2005;Schulz et al 2006;Kiéc-Wilk et al, 2007]. Most mutations are located at the 3' end of the gene between exons 24 and 30.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 150 mutations in ABCC6 have been reported [Bergen et al, 2000;Le Saux et al, 2000;Ringpfeil et al, 2000;Struk et al, 2000;Le Saux et al, 2001;Cai et al, 2001;Meloni et al, 2001;Ringpfeil et al, 2001;Le Saux et al, 2002;Hu et al, 2003b;Chassaing et al, 2004;Gheduzzi et al, 2004;Noji et al, 2004;Chassaing et al, 2005;Hendig et al, 2005;Katona et al, 2005;Miksch et al, 2005;Schulz et al 2006;Kiéc-Wilk et al, 2007]. Most mutations are located at the 3' end of the gene between exons 24 and 30.…”
Section: Introductionmentioning
confidence: 99%
“…PXE is a rare heritable disorder characterized by progressive dermal, ocular and cardiovascular abnormalities that arise through connective tissue alterations and mineralization of elastic fibers [9][10][11][12], which suggested that the lack of ABCC6 function relates to either elastic fibers maintenance or deposition. To date, more than 100 mutations have been characterized in PXE patients [13][14][15][16][17][18]. Most nucleotide variants cluster in specific regions of ABCC6, notably the ATP-binding domains, suggesting that the PXE result lack of transport activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a total of 122 causative ABCC6 mutations has been identified in PXE patients of different origins (Le Saux et al, 2001;Hu et al, 2003;Gheduzzi et al, 2004;Götting et al, 2004;Noji et al, 2004;Chassaing et al, 2005;Hendig et al, 2005;Katona et al, 2005;Miksch et al, 2005;Schulz et al, 2005a). These include missense, nonsense and splice site mutations, as well as deletions and insertions.…”
Section: Introductionmentioning
confidence: 99%